PENANGANAN CUMI-CUMI (Loligo Sp) DIATAS KAPAL PENANGKAP KM. BANDAR NELAYAN 118 - Jhon Septin Mourisdo Siregar; Irandha C. M. Siahaan; Noventius Manek (Universitas Mataram, 2026)
Fish handling is a series of treatments carried out on fish without changing the basic nature of the fish itself. Handling the catch quickly and carefully on board is very important to maintain the freshness of fish and squid. The importance of handling the catch is because fish and squid are commodities that are easily damaged if not handled properly. KM. Bandar Nelayan 118 is one of the types of fishing vessels that focus on catching squid (loligo sp). This study aims to determine the process of handling squid (loligo sp) on a squid fishing vessel. This study was conducted on the KM. Bandar Nelayan 118 fishing vessel anchored at Benoa Harbor, Bali. The method used in this study is qualitative analysis by directly following the process of handling squid on board. From the results of observations during the study it was known that the handling of squid on board KM. Bandar Nelayan 118 consisted of; storage in baskets, weighing, sorting, washing, arranging on trays, arranging and freezing in cast iron to loading and unloading squid in the middle of the sea.